Economic Viability of Electric Bus Adoption for Public Transportation in Thailand: A Monte Carlo Simulation Approach - Sakgasem Ramingwong; Sate Sampattagul; Jutamat Jintana (Logistics, 2025)
Background: Thailand is actively transitioning toward electric vehicle adoption as part of its commitment to reducing greenhouse gas emissions. This study investigates the economic feasibility of replacing diesel buses with electric buses in Thailand’s public transportation sector. Methods: The research employs a comprehensive methodological framework combining Total Cost of Ownership (TCO) analysis with Monte Carlo simulation to address uncertainties in long-term financial projections. The study examines four pilot routes operated by a major Thai bus company, incorporating potential carbon credit revenues through Thailand’s Voluntary Emission Reduction program. Results: The analysis reveals substantial cost advantages for electric buses across all examined routes, with TCO savings ranging from 23.07% to 38.25%. Even under conservative scenarios, all routes demonstrate positive economic benefits. The fleet-wide net savings amount to approximately 236 million THB over a 10-year period, with an additional 16.7 million THB potential carbon credit revenue. Sensitivity analysis identifies fuel costs as the most significant factor (45.2%) affecting economic outcomes. Conclusions: The transition to electric buses presents a compelling economic and environmental case for Thai public transportation operators, with significant cost savings and emission reductions. A phased implementation approach beginning with routes offering the highest percentage savings is recommended.